قرآنی تناظر میں زوال کی وجوہات: پاکستانی معاشرے اور سابقہ اقوام کا تقابلی مطالعہ : Quranic Perspective on the Causes of Decline: A Comparative Analysis of Pakistani Society and Past Nations - Dr. Shazia; Sara Shafiq (Al Manhal Research Journal, 2025)
The Holy Quran is a universal Book of guidance that addresses all aspects of human life, both individual and collective. It calls mankind towards righteousness, warns against evil, and recounts the histories of past nations as lessons of admonition. The mission of the Prophets (peace be upon them) and the disobedience of their peoples form central Quranic themes, intended to guide the Ummah. The idol worship of the people of Nuh (A.S.) and Ibrahim (A.S.), the immorality of the people of Lut (A.S.), the arrogance of ‘Ad and Thamud, the fraudulent dealings of Shuayb’s (A.S.) people, and the ingratitude of Bani Israel are not merely historical episodes but recurring patterns that reappear in contemporary societies, including Pakistan. This article presents a comparative analysis of these narratives in the Quran and the conditions of Pakistani society, showing that estrangement from faith, moral corruption, injustice, and materialism remain the enduring causes of decline. It concludes that true success lies in adherence to Divine commandments and Prophetic teachings, while deviation leads to inevitable downfall, as history testifies.